2016
DOI: 10.1371/journal.pone.0163194
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of Angraecum (Orchidaceae, Vandeae) in Madagascar: Revised Phylogeny Reveals Species Accumulation through Time Rather than Rapid Radiation

Abstract: Angraecum is the largest genus of subtribe Angraecinae (Orchidaceae) with about 221 species. Madagascar is the center of the diversity for the genus with ca. 142 species, of which 90% are endemic. The great morphological diversity associated with species diversification in the genus on the island of Madagascar offers valuable insights for macroevolutionary studies. Phylogenies of the Angraecinae have been published but a lack of taxon and character sampling and their limited taxonomic resolution limit their us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…In fact, African species of Angraecum belong to a group clearly distinct from that of members of the genus in Madagascar and the Indian Ocean islands ( Micheneau et al 2008 ). While investigating the diversification of the genus in Madagascar, Andriananjamanantsoa et al (2016) also confirmed the polyphyly of Angraecum s.l. and of all Angraecum sections with representatives in Madagascar, with the sole exception of section Hadrangis Schltr.…”
Section: Introductionmentioning
confidence: 55%
“…In fact, African species of Angraecum belong to a group clearly distinct from that of members of the genus in Madagascar and the Indian Ocean islands ( Micheneau et al 2008 ). While investigating the diversification of the genus in Madagascar, Andriananjamanantsoa et al (2016) also confirmed the polyphyly of Angraecum s.l. and of all Angraecum sections with representatives in Madagascar, with the sole exception of section Hadrangis Schltr.…”
Section: Introductionmentioning
confidence: 55%
“…However, we found no strong (unambiguous) evidence for such a potential link between inferred historical changes in CO 2 (or temperature) and diversification across the full tree, and not at all for subclade C (Table S5). However, the crown age of this subclade and its corresponding shifts towards CAM and into the Eastern Lowlands (c. 7.36 Ma) remarkably coincide with the strengthening of the Indian Summer monsoon (c. 7 Ma; Gupta et al, 2015), resulting in increased moisture levels throughout eastern Madagascar and, possibly, the establishment of the Northwest 'Sambirano' (Yoder & Nowak, 2006;Buerki et al, 2013;Andriananjamanantsoa et al, 2016). In addition, these changes in monsoon climate could have created environmental instability across the comparatively older sub-humid and humid forest biomes of the Central Highlands and Eastern Coast of Madagascar, respectively (Cornet, 1974;Buerki et al, 2013).…”
Section: Major Transition From C 3 To Cam Associated With Invasion Of High Rainfall Forestmentioning
confidence: 93%
“…32.48 Mya, min. 22.2 Mya) we used published divergence times ( Givnish et al, 2015 ; Andriananjamanantsoa et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%